Martin Luther and Philip Melanchthon on the care and feeding of [future] Pastors. Issue 2 (23rd May 2020) - Wengert, Timothy J.
Abstract: This article argues that humanist training was all‐encompassing, not just for Philip Melanchthon but also for Martin Luther. By reexamining the relationship between the two reformers in this area, the article shows how their substantial, overarching agreements, especially in matters of pedagogy, led to a single‐minded reform of Wittenberg's curriculum. Finally, it argues that their revolutionary approach to seminary training also addresses its collapse in our own day.